Influence of Cinnamic Acid, Methyldopa and Ethanol‎ on the ‎readings of Three Glucometers Currently ‎Used in Iraq - Esraa Ghazy; Ayat K. Abdulellah; Hayder R. Fadhil; Farah Hashim; Mohammed Alawami; Zainab Emad (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Dibetes mellitus represents a major public health concern carrying a high rate of morbidity and mortality. Its complications are highly prevalent and might be inevitable in certain circumstances, and the proper monitoring of patients might be the only weapon to minimize these complications. Self-monitoring with a glucometer is the most widely used method for such an issue. The accuracy of these devices has been always a subject of huge debate. The current study aimed to investigate any potential interfering effect of cinnamic acid, methyldopa and ethanol on the measurement of blood glucose estimated by certain glucometers; Accu-chek‎instant, Rossmax HS-‎‎200‎ and Oncall plus. Method:A total of 8ml of blood from a non-fasting participant was drawn after collecting consent, which was then collected in the lithium-heparin tube and centrifuged to isolate blood plasma, divided into 2 groups each spiked with interferants (methyldopa, cinnamic acid). For ethanol, the procedure is different, a participant’s finger was sprayed with 70% ethanol, before the alcohol dries, we lance the finger and test the level of interference by comparing the reading to the baseline. The obtained results were statistically evaluated using Paired T-test. Results:The presence of cinnamic acid resulted in a significant increase in glucometer readings compared to the baseline reading. The presence of topical 70% ethanol also result in a significant difference in glucometer readings compared to the baseline reading. The presence of methyldopa resulted in a significant decrease in Accu-chek instant compared to the baseline reading but not for Oncall plus or Rossmax HS-200. Conclusion : all three glucometers were significantly affected by cinnamic acid and topical ethanol 70%, while only the Accu-chek instant was affected by methyldopa.